Gender equality in science, technology, engineering and mathematics: industrial vis-a-vis academic perspective - Antigoni Parmaxi; Eirini Christou; Julia Fernández Valdés; Dalia María Puente Hevia; Maria Perifanou; Anastasios A. Economides; Jelena Mazaj; Maryna Manchenko (Springer, 2024)
Abstract The aim of this study is to present the findings of a qualitative study aiming at capturing key stakeholders' perceptions with regard to: (a) gender equality in academia and the workplace; (b) challenges, needs, and experiences in academia and workplace with regard to gender. This research captures the current situation of gender equality in the fields of Science, Technology, Engineering and Mathematics (STEM) and provides a deep understanding of the needs, challenges and experiences both men and women encounter in academia vis-a-vis the industry. Forty-one interviews were conducted in Cyprus, Greece, Italy, Slovenia, and Spain. Data collected demonstrate a variety of challenges faced by all genders in the workplace and in academia, as well as the need for more concrete actions that will allow for a gender-balanced perspective to be heard in the STEM fields. Implications for practitioners, policymakers and researchers are also provided.